STRATEGI TATA BANGUNAN PADA RUMAH TAHANAN KELAS IIB HUMBANG HASUNDUTAN - Simatupang, Jessica Tio Minar; Padmono, Padmono (Yustitia, 2022)
This study aims to determine the strategy of building design in Humbang Hasundutan Rutan Class IIB. The type of research used is normative-empirical research. Primary data from specialist interviews and secondary data from literature study were used as data types. The data obtained from the study were analyzed using qualitative methods with descriptive decomposition. Based on the results of the study, it was found that the concept of the Humbang Hasundutan Class IIB Rutan building was not in accordance with the standards for the type of prison technical implementing unit, as stated in the Decree of the Minister of Law and Humanity No. M. 01. OT. 01/01/2003 concerning the Technical Correctional Institution Development Plan and the Details of the Population Assessment Standards according to the Decree of the Director General of Corrections Number PAS-499. NS. 02.03.01 of 2015 concerning Standards for Assessment of Rutan or Prison Employees. The set of policies and regulations that implement the prison system requires housing assessments as a tool to gather information and determine actual versus expected situations.